Identification of Coral Reef Health Conditions to Support Sustainable Coastal Management in Sopura Bay - Wijayanto, Cahyo; Gazali, Muhammad; Sanjaya, Muhammad Din Hamdan (Sebatik, 2025)
Coral reefs play a vital role in maintaining marine ecosystem balance and supporting biodiversity. This study aims to identify the coral reef health condition in Sopura Bay and formulate sustainable coastal management strategies. The methods used include the Coral Health Chart (CoralWatch) to assess coral physiological conditions and SWOT analysis to develop management strategies. The results show that the dominant coral type is massive (Boulder) coral with an average color score of 2–3, indicating moderate to severe bleaching. Environmental stressors such as sedimentation and anthropogenic activities were identified as major causes of coral health decline. The SWOT analysis placed Sopura Bay in the Turn Around Strategy position, emphasizing the optimization of strengths (regulation, community initiatives, ecotourism potential) and opportunities (multi-stakeholder collaboration, CSR funding) to overcome weaknesses and minimize threats. Strengthening local capacity through community-based management and educational ecotourism development is recommended to support ecosystem sustainability.